Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/nau.23255
|View full text |Cite
|
Sign up to set email alerts
|

Sacral neuromodulation for detrusor hyperactivity with impaired contractility

Abstract: Twenty patients underwent stage 1 trial of SNM for DHIC. Median age was 68.5, IQR (54.25-76.25). Thirteen (65%) patients were female. A total of 14/20 (70%) of patients had a significant treatment response, 9/20 had a response to both elements of DHIC, 4/20 patients had a response to the detrusor overactivity (DO) alone, and 1/20 had a response to the voiding component alone. A total of 12/20 (60%) patients proceeded to insertion of an IPG. At mean follow-up of 17 months, IQR (1.5-35), 11/12 (91.7%) of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Sacral neuromodulation has the potential to control both UUI and compromised detrusor contractile function. Hennessey and Hoag reported that sacral neuromodulation for patients with DHIC could ameliorate OAB symptoms and decrease in PVR although they did not show an improvement in UUI due to the small patient numbers [ 43 ].…”
Section: Managementmentioning
confidence: 99%
“…Sacral neuromodulation has the potential to control both UUI and compromised detrusor contractile function. Hennessey and Hoag reported that sacral neuromodulation for patients with DHIC could ameliorate OAB symptoms and decrease in PVR although they did not show an improvement in UUI due to the small patient numbers [ 43 ].…”
Section: Managementmentioning
confidence: 99%
“…One could hypothesize that identifying DU could impact treatment decision-making as well. Indeed, recent series suggested that the safety and efficacy of sacral neuromodulation was preserved in patients with DU and coexisting DO while intradetrusor botulinum toxin injections was less effective in this subgroup [26,27]. Hypothetically, urodynamic findings might influence the selection of several other treatment options (beta 3 agonist vs. anticholinergics in obstructed vs. unobstructed, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Bladder contractility significantly improved following SNM in a cohort with detrusor underactivity who had “detrusor hypocontractility” on urodynamics . In a cohort of patients with detrusor overactivity with impaired contractility (DHIC), a typical condition in the elderly, 70% undergoing test stimulation showed a treatment response and both DO during filling and DU during voiding improved …”
Section: Assessmentmentioning
confidence: 99%